Low Density Polyethylene (LDPE)/ Thermoplastic Sago Starch (TPSS) blend Filled Kenaf Core Fiber (KCF) - Sarifuddin, Norshahida; Ismail , Hanafi; Ahmad, Zuraida (Trans Tech Publications, Switzerland, 2013)
Recently, blending of common hydrocarbon polymer with natural based materials has gain much interest towards the development of degradable composites. In this study, a series of LDPE/TPSS blend reinforced with KCF with stach content ranging from 10 to 40% were prepared via melt blending method. For this study, kenaf loading was fixed at 20% (by weight). The blended samples were characterised by means of tensile test and morphological study. The experimental results shows that there is a gradual decrease in tensile strength, modulus and elongation at break with increase in starch loading. The scanning electron micrograph supports the findings of tensile properties.